The Protection of Polysaccharide from the Brown Seaweed Sargassum graminifolium against Ethylene Glycol-Induced Mitochondrial Damage - Wen-Hui Wu; Min-Bo Lan; Ting Kong; Chao-Yan Zhang (Marine Drugs, 2013)
The aim of the present study is to evaluate the protective effect of polysaccharide from the Brown Seaweed Sargassum graminifolium (SGP) on ethylene glycol-induced kidney damage and the mechanism of SGP-mediated protection. Mitochondrial lipid peroxidation, mitochondrial swelling, the activity of succinate dehydrogenase (SDH), ATPases and mitochondrial antioxidant enzymes was observed in hyperoxaluric rats. Administration of SGP (25, 100 and 400 mg·kg−1, intragastrically) increased the activities of antioxidant enzymes, SDH and Na+/K+-ATPases, Ca2+-ATPases, Mg2+-ATPases, also decreased mitochondrial lipid peroxidation and mitochondrial swelling. SGP exhibited a protective effect by improving antioxidant enzymes and restoring mitochondrial dysfunction in the kidney of hyperoxaluric rats. It may be used as a promising therapeutic agent to provide superior renal protection.